2019
DOI: 10.1016/j.neuroimage.2018.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebral blood flow after single dose of antipsychotics in healthy volunteers depends on dopamine D2 receptor density profiles

Abstract: Increased cerebral blood flow after single dose of antipsychotics in healthy volunteers depends on dopamine D2 receptor density profiles. NeuroImage, 188, 774-784.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 72 publications
(115 reference statements)
1
33
0
Order By: Relevance
“…Assuming affinity to a certain target is constant across regions, this basic pharmacology principle predicts that brain regions of high density of the target receptor will show higher magnitude of drug effects. This relationship has been demonstrated for compounds targeting the dopamine, glutamate, serotonin and GABA systems 116,117 . However, we are still unclear about whether and how the physiological brain changes (i.e.…”
Section: Relationship Between Intranasal Oxytocin-induced Changes In Rcbf and The Expression Of Oxtr Mrnamentioning
confidence: 85%
“…Assuming affinity to a certain target is constant across regions, this basic pharmacology principle predicts that brain regions of high density of the target receptor will show higher magnitude of drug effects. This relationship has been demonstrated for compounds targeting the dopamine, glutamate, serotonin and GABA systems 116,117 . However, we are still unclear about whether and how the physiological brain changes (i.e.…”
Section: Relationship Between Intranasal Oxytocin-induced Changes In Rcbf and The Expression Of Oxtr Mrnamentioning
confidence: 85%
“…The integration between haemodynamic markers and molecular imaging data is still a challenge. Some studies investigated the spatial association between the main effects of different drugs on the CBF and the molecular information from gene-expression, PET or autoradiography data using simple ROI-to-ROI correlations (Dukart et al., 2018; Selvaggi et al., 2018). While this approach has proven its efficacy with ASL data sets, it would be over simplistic if applied to rs-fMRI data, since the temporal dynamics of the BOLD signal would be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest effects observed with low dose rather associate with DAT, SERT and D1 receptor maps. In our previous study (Selvaggi et al, 2018) we observed correlations with D2 receptors at both doses for the group averaged data. This study did not examine effects using other targets and did not evaluate individual differences.…”
Section: Conclusion From the Application Examplesmentioning
confidence: 67%
“…Whilst providing information about the spatial location of respective signals, such analyses do not allow drawing conclusions on potential neurophysiological mechanisms underlying the observed associations. To overcome this limitation, several recently published studies made use of spatial associations between underlying biology and observed imaging alterations by correlating ex vivo micro RNA spatial expression patterns with different imaging measures (Liu et al, 2019;Rizzo et al, 2016;Selvaggi et al, 2018). The major idea behind such analyses is that disease-or drug-induced changes in imaging measures occur in association with availability of a specific tissue property (i.e.…”
Section: Introductionmentioning
confidence: 99%